An NMR method for studying the kinetics of metal exchange in biomolecular systems. - Barbieri, R; Hore, P; Luchina, C; Pierattelli, R (2002)
The kinetics of lanthanide (III) exchange for calcium(II) in the C-terminal EF-hand of the protein calbindin D9k have been studied by one-dimensional (1D) stopped-flow NMR. By choosing a paramagnetic lanthanide (Ce3+), kinetics in the sub-second range can be easily measured. This is made possible by the fact that (i) the kinetic behaviour of hyperfine shifted signals can be monitored in ID NMR and (ii) fast repetition rates can be employed because these hyperfine shifted signals relax fast. It is found that the Ce3+-Ca2+ exchange process indeed takes place on a sub-second timescale and can be easily monitored with this technique. As the rate of calcium-cerium substitution was found not to depend on the presence of excess calcium in solution, the kinetics of the process were interpreted in terms of a bimolecular associative mechanism, and the rate constants extracted. Interestingly, the dissociative mechanism involving the apo form of the protein, which is generally assumed for metal ion exchange at protein binding sites, was not in agreement with our data.